The Use of Think-Pair-Share Technique to improve reading comprehension of seventh grade Students of SMP Negeri 10 Parepare: Think-Pair-Share Technique improve the Students Reading Comprehension at SMP Negeri 10 Parepare - Alfandi, Alfandi (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
Reading skill is increasingly seen as one of the most important skills because mastering reading skill, the student will be easier to understand the meaning of the text. The skill of reading a variety of texts will enable learners to adjust the speed and style of their reading to suit the purpose and extract both implicit and explicit meaning from the text. Therefore, reading skill is still one of the most important aspects to be taught in school in order to enable the learners to grasp the meaning from the reading text. Reading without comprehension or understanding is not reading, many students can pronounce words fluently but when asked what they have just read, they are unable to respond. This research was based on the students problem regarding the English teaching, especially the students reading comprehension. It was caused by the teaching activity applied in the classroom, where the teacher was more active than the students. Consequently, the students reading was low. Therefore, the objective of the research to find out whether or not the use of Think-Pair-Share technique improves the seventh students of SMP Negeri 10 Parepare. The researcher applied quasi-experimental design, with two groups pretest and posttest design. The population of this research was the seventh grade students at SMP Negeri 10 Parepare academic year 2018/2019. The sample of research was taken by using total random sampling which consisted of 64 students from two classes taken from the population of the seventh grade students of SMP Negeri 10 Parepare, VII.1 as the experimental class and VII.3 as the control class. The result of the data analysis showed that the students reading comprehension was improved, it was showed by the mean score of pretest in experimental class was 52,58 while the contol class 46,66. Besides that the mean score of posttest on experimental 72,58 while on control class 63,33. It proved the t-test 2.166 is grater than t-table 2.000 with degree of freedom (df) = (N1+N2-2) 62 for 0.05 level of significance. It showed that the reading comprehension of the seventh grade students at SMP Negeri 10 Parepare improved by using Think-Pair-Share technique.